Stochastic Finite Element Technique For Solving A Class Of SDE - Mouna, sayah; zohra, kertiou (My University, 2022)
Dans ce mémoire, nous avons présenté la méthode des éléments finis stochastiques , où nous avons abordé les aspects les plus importants des processus stochastiques communs et aussi la théorie de Lax-Milgram dans le ntionné les méthodes stochastiques les plus importantes pour résoudre les équations différentielles stochastiques, méthode de Monte Carlo, méthode de quadrature, méthode de perturbation, où nous avons appliqué this memory, we presented the method of elements finite stochastic, where we touched on the most important common stochastic processes and also the theory of Lax-Milgram in the deterministic element finite method to prove the existence and uniqueness of the solution. We also mentioned the most important stochastic methods for solving stochastic differential equations ( Monte Carlo method, quadrature method, perturbation method), where we applied some of them in mechanics, especially in geo-techniques and fracture mechanics.certaines des en mécanique, notamment en géotechniques et en mécanique de la rupture.In this memory, we presented the method of elements finite stochastic, where we touched on the most important common stochastic processes and also the theory of Lax-Milgram in the deterministic element finite method to prove the existence and uniqueness of the solution. We also mentioned the most important stochastic methods for solving stochastic differential equations ( Monte Carlo method, quadrature method, perturbation method), where we applied some of them in mechanics, especially in geo-techniques and fracture mechanics.
memorie master mathematique
Keywords: Stochastic processes, the element finite method, elements finites stochastic meth- ods, Monte Carlo method, quadrature method, perturbation method.; Processus stochastiques, des éléments finie méthode, éléments finies stochastiques méthodes (méthode de Monte Carlo, méthode de quadrature, méthode de perturbation).